The secret birthday message - Carle, Eric. ([New York] : HarperCollins, 1986)
By following the instructions in the coded message, Tim finds his birthday present.
Book Links (A.L.A.).
Reference and Research Book News.
2.7.
2.7
K-3
Keywords: Toy and movable books -- Specimens; Birthdays -- Fiction; Cryptography -- Fiction; Toy and movable books; Birthdays -- Fiction; Cryptography -- Fiction; Toy and movable books